The Application of Murabaha in Gold Financing (Gold Murabaha) in Indonesian Islamic Banks: Issues and Possible Alternative Model - Marlia, Sri (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2025)
Gold is considered one of the most precious metals in the world due to its upward price trend. This reason encourages people to invest in gold. In Indonesia, some Islamic banks offer the product related to this kind of investment under a murabaha contract with deferred payment basis or instalment. This study examines the application of murābaḥa contracts in gold financing offered by Indonesian Islamic banks. The research aims to identify Sharia compliance issues, particularly concerning deferred payment and physical possession, and to propose alternative models that align more closely with Islamic legal principles. The study employs a qualitative approach, combining doctrinal analysis of Qur’anic and Hadith sources, fatwas issued by the DSN-MUI, and regulatory guidelines with a review of contemporary literature on Islamic finance. Data were collected from Islamic banks’ official websites and product documents, allowing for comparison of Gold Murabaha practices across several institutions. Two major issues are identified in current practice: (1) the use of deferred payment (instalments) in gold exchange, which conflicts with hadith requirements of spot settlement; and (2) questions regarding physical possession and delivery of gold, raising concerns about ownership transfer and the prohibition of ribā al-nasīʾah. The study also proposes a model as an alternative.